1999
DOI: 10.1152/ajplung.1999.276.1.l75
|View full text |Cite
|
Sign up to set email alerts
|

Ion transport in epithelial spheroids derived from human airway cells

Abstract: In the present study, we describe a novel three-dimensional airway epithelial explant preparation and demonstrate its use for ion transport studies by electrophysiological technique. Suspension cultures of sheets of epithelial cells released by protease treatment from cystic fibrosis (CF) and non-CF nasal polyps developed free-floating, monolayered epithelial spheres, with the apical, ciliated cell membrane facing the bath and the basolateral cell membrane pointing toward a fluid-filled lumen. Microelectrode i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 24 publications
8
35
1
1
Order By: Relevance
“…The apical membranes face the outside, and basolateral membranes line the lumen of the spherical organoids ( Figure 1). This orientation has been observed by other groups when nondisrupted epithelial sheets are cultured in suspension (40)(41)(42)(43)(44). When CFTR is labeled with a highly specific monoclonal antibody raised against the NBD2 region of CFTR (Ab 528, provided by J.R. Riordan, UNC-Chapel Hill; refs.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…The apical membranes face the outside, and basolateral membranes line the lumen of the spherical organoids ( Figure 1). This orientation has been observed by other groups when nondisrupted epithelial sheets are cultured in suspension (40)(41)(42)(43)(44). When CFTR is labeled with a highly specific monoclonal antibody raised against the NBD2 region of CFTR (Ab 528, provided by J.R. Riordan, UNC-Chapel Hill; refs.…”
Section: Resultssupporting
confidence: 63%
“…First, we tested non-CF spheroids derived from normal human nasal epithelium (Figure 2). Volume changes in similar spheroids have previously been reported in response to fluid transport changes (40)(41)(42)(43). To test our hypothesis that CFTR activation leads to fluid movement and consequent volume changes of the nasospheroids, we applied forskolin (10 μM) and 3-isobutyl-1-methylxanthine (IBMX,100 μM), a phosphodiesterase inhibitor that maintains intracellular cAMP levels (51), leading to CFTR activation in a cAMP-dependent manner ( Figure 2A).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Several investigators have previously shown that epithelial sheets, dissociated from adult airway surface epithelium, nasal brushings, or nasal polyps and cultured in suspension spontaneously reform free-floating epithelial spheroids in which ciliary activity and ion transport functions could be maintained for several months (Bridges et al, 1991;Jorissen et al, 1991;Pedersen et al, 1999;Ulrich et al, 1998). In all of these studies, the native well-organized surface epithelial cell structures were preserved and no information could therefore be obtained on the depolarization and repolarization process.…”
Section: Discussionmentioning
confidence: 99%
“…To retain the differentiated and polarized state of the epithelium, several investigators have developed a three-dimensional (3-D) culture model in which epithelial sheets derived from human airway cells form free-floating epithelial spheroids in which ciliary activity and ion transports can be preserved for several months (Jorissen et al, 1989;Pedersen et al, 1999;Ulrich et al, 1998).…”
mentioning
confidence: 99%